Desain Brand Identity Coconut Orchids Nursery - Nur Hakim, Fitro; Rizqa Naja, Adi (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Identity is a way that distinguishes the character or innate nature of living things, things, or humans themselves that characterize them. Brand Identity is a sign of identifying an identity of a brand as a differentiator from other brands. Brand Identity design can be notarized successfully when the brand identity represents a brand, in its delivery in the form of logos, applications, on stationary sets and on promotional media.Coconut Orchids Nursery is an orchid flower cultivation place that has a fairly complete orchid collection. Coconut Orchids Nursery plans to develop its business. In order for the planning to be measurable, it is necessary to design strategic planning in the form of strategy plots and work programs. Brand identity design is needed as a standard strategy program in a business / company. In order to be effective, a brand identity must be distinguishable from competing brands and be able to represent the product, service, or company over time. Efforts in achieving brand identity must be done with full commitment and consistency because the benefits will be worth it if successful.